Antioxidant, α-glucosidase inhibitory, and cytotoxic activities of Mangifera rufocostata extract and identification of its compounds by LC-MS/ MS analysis - Mustikasari, Kamilia; Santoso, Mardi; Abu Bakar, Mohd Fadzelly; Sri Fatmawati, Sri Fatmawati (2024)
Mangifera rufocostata, a member of the Mangifera genus, is a source of secondary metabolites and has been used traditionally as antidiabetic agent. Therefore, this study aims to determine the total flavonoid contens (TFC), total phenolic contents (TPC), antioxidant, α-glucosidase inhibitory, and cytotoxic activities of M. rufocostata stem bark extract. Antioxidant activity were evaluated by 2-2″-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 1,1-diphenyl-2-picrylhydrazyl (DPPH), and ferric reducing-antioxidant power (FRAP) tests. α-glucosidase inhibitory to prediction antidiabetic activity, and cytotoxic activity were studied against HT-29, HeLa, and MCF-7 cancer cell lines. The results showed that the methanol extract have the highest TFC, TPC, antioxidant, and α-glucosidase inhibitory activity. Furthermore, the methanol extract has strong cytotoxicity againts HT-29 cancer cells. Based on LC-MS/MS, the methanol extract contain several major compounds such as mangiferin, quinic acid, gallic acid, and 3-methoxy-4-hydroxy-phenyl glycol.